Diversification des territorialités autochtones contemporaines : réflexions sur l’accès à la propriété privée chez les Nisga’a de Colombie-Britannique - Bastien Sepúlveda (Cahiers de géographie du Québec, 2013)
Under recent agreements with the federal and provincial governments of Canada, the autonomy gained by some First Nations allows them to make significant changes in their territorial relations, a key factor in their political reaffirmation. Some of these advances draw on the cultural interpenetration of Indigenous and non-Indigenous ways of thinking about and understanding the land. In doing so, they tangibly reassert the relationships First Nations have traditionally maintained with their land. As part of this article, we focus specifically on initiatives affecting property rights within the Nisga’a Nation. Moreover, we show how access to private property may be challenging some aspects of culture and identity through scalar restructuring. When the concept of private property extends beyond its purely legal expression and becomes symbolic, it generates its own concomitant living practices. That said, in a context where the lifestyles and living environments of Indigenous people are becoming more diverse and fragmented, territoriality is constantly being redefined. We therefore examine whether and how private property on the Nisga’a residential territories can meet their economic and politic aspirations as well and foster their cultural affirmation, while remaining rooted, in part, in an exogenous ontological structure. En vertu d’ententes conclues récemment avec les différents paliers gouvernementaux canadiens, l’autonomie acquise par certains groupes autochtones permet à ces derniers de réaliser des changements considérables sur le plan de leurs relations territoriales, actrices et témoins de leur réaffirmation politique. Certaines de ces avancées participent en effet d’une interpénétration culturelle qui interpelle des modes autochtones et non autochtones de penser et de concevoir le territoire. Ce faisant, elles réinvestissent la nature même des relations que les Premières Nations entretiennent avec celui-ci. Dans le cadre de cet article, nous nous intéressons plus précisément aux initiatives conditionnant ...